Modifying Effect of N‐Acetyltransferase 2 Genotype on the Association Between Systemic Lupus Erythematosus and Consumption of Alcohol and Caffeine‐Rich Beverages. Issue 7 (July 2014) - Kiyohara, Chikako; Washio, Masakazu; Horiuchi, Takahiko; Asami, Toyoko; Ide, Saburo; Atsumi, Tatsuya; Kobashi, Gen; Takahashi, Hiroki; Tada, Yoshifumi; the Kyushu Sapporo SLE (KYSS) Study Group
<x xml:space="preserve">Abstract</x> Objective N‐acetyltransferase 2 (NAT2) is involved in the metabolism of various environmental substances, both with and without carcinogenic potential. Alcoholic and nonalcoholic caffeine‐rich beverages may be associated with markers of inflammation. Systemic lupus erythematosus (SLE) is a chronic, multifaceted inflammatory disease. We investigated the effects of alcoholic and nonalcoholic caffeine‐rich beverages on risk of SLE and determined whether the effects were modified by NAT2 status. Methods The NAT2 polymorphism was genotyped in 152 SLE cases and 427 healthy controls, all women and Japanese. We assessed effect modification by testing an interaction term for the NAT2 polymorphism and consumption of beverages. Results Consumption of black tea (odds ratio [OR] 1.88, 95% confidence interval [95% CI] 1.03–3.41) and coffee (OR 1.57, 95% CI 0.95–2.61), but not green tea, was associated with an increased risk of SLE, while alcohol use (OR 0.33, 95% CI 0.20–0.55) was associated with a decreased risk of SLE. There were significant interactions between the NAT2 polymorphism and either alcohol use (Pinteraction = 0.026) or consumption of black tea (Pinteraction = 0.048). Conclusion The NAT2 polymorphism significantly modified the effects of alcohol use and black tea consumption on SLE, emphasizing the importance of incorporating genetic and metabolic information in studies on management of SLE. Additional studies are warranted to confirm the findings suggested in this study.